Group size affects social relationships in yellow-bellied marmots (Marmota flaviventris) (2015)
Demographic variation, such as changes in population size, affects group-living conditions and thus creates new opportunities for individuals to interact socially. To understand how this variation in the social environment affects social structure, we used social network analysis to explore affiliative behaviors of nonpup (i.e., 1 year or older), female, yellow-bellied marmots (Marmota flaviventris). We examined 4 social attributes (outdegree, indegree, closeness centrality, and betweenness centrality) to measure social plasticity in response to group size variation. We found that, in response to increases in group size, individuals established fewer social connections than possible, which suggests that marmots experience constraints on sociality. Similarly, closeness and betweenness centrality decreased as group size increased, suggesting that females are expected to lose influence over other members of the group as group size increases, and there are substantial constraints on marmots transmitting information to others in large groups. Our results also suggest that group-level responses, such as behavioral plasticity, can be explained by individual-level mechanisms that evaluate the costs and benefits of sociality. Interestingly, the mechanistic basis of these group-level responses may, at times, follow patterns expected by chance. We propose that further research is necessary to uncover the mechanisms underlying the individual-level behavioral response. Like group size effects studied in other domains, formally considering group size effects on social structure may shed novel light on the constraints on sociality.